Continuity and export performance in Peruvian companies (Journal of Business, Universidad del Pacífico (Lima, Peru), 2013)
This paper studies the relationship between continuity of business in international markets and their export performance. For this, the paper focuses on the Peruvian export companies during the period 2000-2008, stage where Peruvian exports had continued growth. the results achieved in international markets are analyzed and through probabilistic logit model establishes the relationship between continuity in these markets and the export performance measured in export sales.